2022
DOI: 10.1177/23259671221088049
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Anterolateral Ligament Reconstruction and Lateral Extra-articular Tenodesis With ACL Reconstruction in Children and Adolescents

Abstract: Background: Anterolateral ligament reconstruction (ALLR) and lateral extra-articular tenodesis (LET) show promise in lowering the risk of rerupture after anterior cruciate ligament reconstruction (ACLR), but there are little data on surgeon practices and preferences in children and adolescents. Purpose: To quantify surgeon practices regarding ALLR and LET in the pediatric population. Study Design: Cross-sectional study. Methods: An electronic survey was administered to 87 surgeons in the Pediatric Research in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In recent years there has been an increasing interest in lateral extra-articular procedures in pediatric patients with an ACL injury [ 46 , 47 ]. A recent survey among American orthopaedic surgeons has shown that 56% performed an anterolateral augmentation with primary ACL reconstruction in rare cases, and 79% in revision ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years there has been an increasing interest in lateral extra-articular procedures in pediatric patients with an ACL injury [ 46 , 47 ]. A recent survey among American orthopaedic surgeons has shown that 56% performed an anterolateral augmentation with primary ACL reconstruction in rare cases, and 79% in revision ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…24 This study revealed that only 56% of surgeons sometimes performed LEAP with primary ACLR and 79% with revision ACLR, with the predominant deterrent being a perceived lack of sufficient evidence to support these practices. 24 The primary aim of this study was to evaluate the rate of rerupture after ACLR in adolescent patients when treated with or without LEAP. The secondary aim of this study was to compare the rates of non-graft rupture related reoperation and functional outcomes of these 2 strategies, considering several patient-reported outcome measures and return to sport (RTS).…”
mentioning
confidence: 89%
“…77 Madhan et al in a recent study children and adolescent patients found that 56% of pediatric sports surgeons sometimes perform anterolateral augmentation with primary ACLR and 79% with revision ACLR. 78 Another systematic review with the meta-analysis by Na et al; found that anterolateral ligament reconstruction (ALLR) appeared to be a better option for improving rotational stability compared than extra-articular tenodesis (LET). 79 However, more prospective comparative studies are needed to assess if there is a significant difference between two surgical techniques with a view to clinical outcomes.…”
Section: Outcomementioning
confidence: 99%